Basics of nuclear medicine imaging - Bailey, Dale (Henry Stewart Talks, 2010)
Basics of nuclear physics used in nuclear medicine, imaging and therapy, Devices used including gamma camera, SPECT and PET imaging, Multimodality imaging devices (SPECT/CT, PET/CT), Radiation dosimetry for nuclear medicine